2021
DOI: 10.1002/ijc.33508
|View full text |Cite
|
Sign up to set email alerts
|

The association of prediagnostic circulating levels of cardiometabolic markers, testosterone and sex hormone‐binding globulin with risk of breast cancer among normal weight postmenopausal women in the UK Biobank

Abstract: Emerging evidence suggests that normal weight postmenopausal women with a relative excess of body fat are at increased breast cancer risk. However, little is known about the associations between obesity‐related blood markers and risk of breast cancer among these individuals. In this prospective study comprising 58 629 normal weight postmenopausal women (body mass index between 18.5 kg/m2 and 24.9 kg/m2) who were enrolled in the UK Biobank cohort between 2006 and 2010, we examined the associations of glycated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 47 publications
5
14
0
Order By: Relevance
“…The association between circulating estradiol and breast cancer was supported by previous studies in premenopausal as well as post-menopausal women (Endogenous Hormones and Breast Cancer Collaborative Group et al 2013 ; Fuhrman et al 2012 ). We further confirmed that high circulating testosterone and low SHBG levels were associated with an increased risk of breast cancer in our study, likely due to aromatase activity in fat tissues for testosterone (de Jong et al 2001 ) and the binding effect of SHBG with estrogen (Arthur et al 2021 ; Missmer et al 2004 ). Additionally, a Mendelian randomization study also suggested SHBG as a causal factor for breast cancer (Dimou et al 2019 ).…”
Section: Discussionsupporting
confidence: 86%
“…The association between circulating estradiol and breast cancer was supported by previous studies in premenopausal as well as post-menopausal women (Endogenous Hormones and Breast Cancer Collaborative Group et al 2013 ; Fuhrman et al 2012 ). We further confirmed that high circulating testosterone and low SHBG levels were associated with an increased risk of breast cancer in our study, likely due to aromatase activity in fat tissues for testosterone (de Jong et al 2001 ) and the binding effect of SHBG with estrogen (Arthur et al 2021 ; Missmer et al 2004 ). Additionally, a Mendelian randomization study also suggested SHBG as a causal factor for breast cancer (Dimou et al 2019 ).…”
Section: Discussionsupporting
confidence: 86%
“…Of the 93 eligible full articles, 26 prospective studies met the inclusion criteria; their key characteristics are shown in Table 1 . Among these studies, 21/26 were cohort studies [ 8 , 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] and 5/26 were nested case control studies [ 33 , 34 , 35 , 36 , 37 ]. Study sample sizes ranged from 594 to 288,057 persons aged >20 years.…”
Section: Resultsmentioning
confidence: 99%
“…The mean follow up period was 12.41 years (range 7 to 26 years). Sixteen of the studies were conducted in European countries [ 8 , 9 , 14 , 15 , 16 , 18 , 24 , 25 , 26 , 28 , 29 , 30 , 32 , 34 , 35 , 36 ], 7 in the USA [ 17 , 19 , 20 , 27 , 31 , 33 , 37 ], 2 in Japan [ 22 , 23 ] and 1 in Korea [ 21 ]. Overall, 1,628,871 women were included in the present meta-analysis, of whom 36,590 were diagnosed with breast cancer during the follow-up period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating levels of C-reactive protein, insulin, leptin, and triglycerides were higher, whereas levels of sex hormone-binding globulin and high-density lipoprotein cholesterol were lower in those in the highest vs. lowest quartiles of trunk fat mass 8 . More recently, we found that high levels of blood C-reactive protein and testosterone or low blood levels of sex hormone-binding globulin were associated with an elevated risk of postmenopausal breast cancer among normal BMI women 9 .…”
Section: Introductionmentioning
confidence: 93%